The food, water, air and fire doctrines in ancient Indian and Greek philosophies from a comparative perspective - Škof, Lenart (Asian studies, 2021)
The main aim of this article lies in the comparison of ancient cosmico-natural elements from the Vedic period with their counterparts in the Presocratics, with a focus on food, air, water and fire. By way of an introduction to the ancient elemental world, we first present the concept of food (anna) as an idiosyncratic Vedic teaching of the ancient ele-ments. This is followed by our first comparison%of Raikva%s natural philosophy of V%yu/pr%%a with Anaximenes%s pneuma/aér teaching in the broader context of both the Vedic and Presocratic teachings on the role of air/breath. Secondly, water as brought to us in panc%gnividy% teaching from B%had%ra%yaka Upani%ad and Ch%ndogya Upani%ad is com-pared to the teaching of the Greek natural philosopher Thales. Finally, the teaching on fire as heat being present in all beings (agni vaiśv%nara) and in relation to cosmic teachings on fire in the ancient Vedic world are compared to Heraclitus% philosophy of fire as an element. Additionally, this article also presents a survey and analysis of some of the key representatives of comparative and intercultural philosophy dealing with the elemental and natural philosophy of ancient India and Greece.
Keywords: air; comparative philosophy; filozofija; filozofija narave; fire; food; hrana; ogenj; philosophy; philosophy of nature; predsokratiki; Presocratics; primerjalna filozofija; Vedic philosophy; vedska filozofija; voda; water; zrak